Hating corrupt people but still acting corruptly : independent predictive effects of social attitudes and worldviews on attitudes towards corrupt people and corrupt intention - Andrade, Felipe Vilanova de Gois (2021)
In many countries, endemic corruption and widespread rejection of corrupt people coexist. Although paradoxical, the frequent co-occurrence of these phenomena indicates that they might be independent and predicted by distinct social attitudes and worldviews. The objective of this thesis was to investigate the differential associations of two independent social attitudes (Social Dominance Orientation [SDO] and Right-Wing Authoritarianism [RWA]) and worldviews (Competitive and Dangerous Worldview Beliefs) with corrupt intention and attitudes towards corrupt people. For that purpose, pre-registered hypotheses were tested across six studies. Results from Study 1 (n = 214) indicated that SDO is a primary predictor of corrupt intention, predicting it with a significantly higher magnitude than the endorsement of general system-justifying beliefs. Study 2 (n = 366) demonstrated that attitudes towards corrupt people are significantly predicted by RWA but not SDO. Using the World Values Survey database, Study 3 (n = 69,578; k = 48) indicated that corrupt intention is significantly predicted by SDO but not by RWA across countries. Study 4 (n = 705) indicated that corrupt intention is significantly predicted by SDO but not RWA, while attitudes towards corrupt people are significantly predicted by RWA but not SDO. Study 5 (n = 305) indicated that experimentally increasing dangerous and competitive worldview beliefs increased corrupt intention, but SDO, RWA and attitudes towards corrupt people remained unaffected. Finally, Study 6 (n = 303) further confirmed the independence of corrupt intention and attitudes towards corrupt people, with corrupt intention primarily predicted by competitive worldview and attitudes towards corrupt people primarily predicted by RWA. In general, the results suggest that corrupt intention and attitudes towards corrupt people are predicted by distinct social attitudes and worldviews, indicating that their psychological and motivational bases are independent. Therefore, the coexistence of these phenomena can be explained by the relative independence of their psychological roots.